The World Summit on Sustainable Development: reaffirming the centrality of health - von Schirnding Yasmin (BMC, 2005)
Abstract The World Summit on Sustainable Development (WSSD) was held in Johannesburg in 2002 to review progress since the Rio conference in 1992, and to agree a new global deal on sustainable development. Unlike its predecessor, it was primarily concerned with implementation rather than with new treaties and targets, although a number of new targets were agreed, for example one on sanitation. Failure to agree a target on renewable energy was regarded as a major disappointment of the conference. While relatively modest in its achievements, and with difficulties in achieving consensus in key areas such as energy, trade, finance and globalisation, WSSD nevertheless succeeded in placing sustainable development back on the political agenda, giving new impetus, in particular to the environment and development needs of Africa, with a strong focus on local issues like household energy, water and sanitation. Health was singled out as one of five priority areas, along with water, energy, agriculture and biodiversity, and was devoted a separate chapter in the resulting Plan of Implementation, which highlighted a range of environmental health issues as well as issues relating to health services, communicable and non-communicable diseases. A number of new partnerships were formed at WSSD, including the Healthy Environments for Children Alliance (HECA) launched by WHO, which will form an important platform for implementation. The Commission on Sustainable Development has been designated main responsibility for monitoring and follow up, with its programme of work reorganised to focus on thematic clusters of issues. From the perspective of health, WSSD must be seen as a reaffirmation of the central place of health on the sustainable development agenda, and in the broader context of a process which began in Rio and was given added impetus with the Monterrey Financing for Development conference and the World Trade Organisation meeting held in Doha. Translating policies into action at all levels- global to local - remains the single biggest challenge in the years that lie ahead.